Pedagogy of 21st century COVID-19 on the rationale of 6000 BCE Indian medical heritage - Konica Gera; Nellufar; Baldev Kumar (Wolters Kluwer Medknow Publications, 2020)
Objective: Ayurvedic texts were documented ages ago, hence they have no specific cure to the diseases of the present day, as they are not described in the texts - this is the most dominant myth which is used to shut the voices of the researchers and practitioners of the Indian System of Medicine. The homo sapiens of the Planet Earth are under the constant fear of a single stranded RNA virus, reported for the first time on December 31, 2019, presenting as pneumonia of unknown origin which broke out exponentially and was declared a public health emergency of international concern on January 30, 2020, further renamed as COVID 19 in place of 2019 Novel Coronavirus on February 11, 2020. This strain is new for the present day researcher as its human transmission is reported for the first time but not for the science which cures the diseased (who are not new) unlike others who seek treatment for the diseases (which are innumerable and keep on emerging). As the virion is Novel and Ayurveda is ages old, these opposites do attract each other, and the present study aims at highlighting the principles laid in the texts of Ayurveda based on which COVID 19 and other newly emerging diseases could be understood and further added to the compendium to pave way for the future researches including drug development for the same. Data Source: SARS CoV 2 and COVID 19 were studied through reliable online sources and published research works. Classical texts of Ayurveda and available commentaries were explored to analyse the Ayurvedic perspective of COVID 19. Review Methods: Analytical review of the analogies was done to establish the hypothesis. Results: Analogies to the spread, transmission, prevention, and control of COVID 19 in texts of Ayurveda could be decrypted and the Etiopathogenesis of the disease based on the principles of Ayurveda was established. Conclusion: COVID 19 was found to be analogues to Vata Kapha Pradhan, Agantuja Abhishangaj jwara of Aupasargika category as per Ayurveda.